Characterization of multi-wavelength polarized light transmission in the real sea spray environment - Luo, Kaiming; Fu, Qiang; Zhang, Yue; Yang, Wei; Zhang, Su; Zhan, Juntong; Li, Zheng; Ma, Yi; Duan, Jin; Jiang, Huilin (Frontiers in Physics, 2023)
Sea spray particles are a type of non-uniform, non-spherical, non-isotropic, and complex medium, and the study of the transmission characteristics of polarized light in a real sea spray environment can provide reference values in many fields, such as polarization imaging, marine target detection, and LiDAR, which can make up for the vacancy of polarized light transmission in a complex sea spray environment. In this paper, a real sea fog test is carried out in the Qingdao Sea area of China in the horizontal/oblique direction, and a platform for generating and detecting polarized light with multiple tilt angles is constructed by using the active test method, which realizes the test scheme for the characteristics of energy change and polarization state change in the linearly polarized light and circularly polarized light at different visibility levels in sea fog environments. The results show that it is more difficult to deflect the circularly polarized light than linearly polarized light at the same sea spray visibility level. With the increase in the tilt angle, a decrease in the polarization is observed. The polarization of the near-infrared light is always larger than that of the visible light, which indicates that the circularly polarized light has better polarization preservation than the linearly polarized light and the polarization preservation of the near-infrared light is better than that of the visible light.